2021
DOI: 10.1016/j.kint.2020.08.023
|View full text |Cite
|
Sign up to set email alerts
|

The sodium/proton exchanger NHA2 regulates blood pressure through a WNK4-NCC dependent pathway in the kidney

Abstract: The sodium/proton exchanger NHA2 regulates blood pressure through a WNK4-NCC dependent pathway in the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 65 publications
(69 reference statements)
2
22
0
Order By: Relevance
“…Based on tissue expression, genome location and phloretin sensitivity, human NHA2 was proposed to be the candidate gene for the Na + (Li + ) countertransport activity associated with the development of essential hypertension and diabetes in humans [9][10][11][12] . Indeed, NHA2 aids in sodium reabsorption in the kidney 13,14 and is a critical component of the with-no-lysine kinase 4-sodium-chloride cotransporter (WNK4-NCC) pathway in the regulation of blood pressure 14 . Furthermore, in vitro and in vivo studies show that NHA2 contributes to β-cell insulin secretion 15 .…”
mentioning
confidence: 99%
“…Based on tissue expression, genome location and phloretin sensitivity, human NHA2 was proposed to be the candidate gene for the Na + (Li + ) countertransport activity associated with the development of essential hypertension and diabetes in humans [9][10][11][12] . Indeed, NHA2 aids in sodium reabsorption in the kidney 13,14 and is a critical component of the with-no-lysine kinase 4-sodium-chloride cotransporter (WNK4-NCC) pathway in the regulation of blood pressure 14 . Furthermore, in vitro and in vivo studies show that NHA2 contributes to β-cell insulin secretion 15 .…”
mentioning
confidence: 99%
“…6B). Since we observed this phenomenon in yeast cells, which may lack some regulatory mechanisms or protein interactions that regulate the activity of Hs NHA2 in mammalian cells (Anderegg et al, 2021), the first 40-50 amino acids of the protein instead perform an autoinhibitory function in Hs NHA2.…”
Section: Resultsmentioning
confidence: 93%
“…In the kidney, NHA2 localizes to distal convoluted tubules, where it is critical for electrolyte (sodium reabsorption) and blood pressure homeostasis (Fuster et al, 2008; Kondapalli et al, 2017). In 2021, Anderegg et al corroborated the NHA2 role in blood pressure regulation in mice, and identified it as critical for the maintenance of serine-threonine with-no-lysine kinase 4 (WNK4) levels, and thus ultimately for the activity of the Na + /Cl − cotransporter NCC in the distal convoluted tubules of the kidney (Anderegg et al, 2021). Increased NHA2 expression also promotes cyst development in an in vitro model of polycystic kidney disease (Prasad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a pancreatic β–cell line, knockdown of NHA2 did not alter endosomal pH ( Deisl et al, 2013 ). Similarly, endosomal and cytoplasmic pH measurements in NHA2-depleted or overexpressing cells did not show NHA2-dependent alterations in renal cell lines ( Anderegg et al, 2021 ). Rao and colleagues suggested chemiosmotic coupling of NHA2 to the proton motive force generated by the V-type H + -ATPase at the plasma membrane of stably-NHA2-transfected MDCK cells, resulting in a virtual Na + efflux pump ( Kondapalli et al, 2012 ).…”
Section: Slc9b2/nha2mentioning
confidence: 83%